2003
DOI: 10.3998/ark.5550190.0004.316
|View full text |Cite
|
Sign up to set email alerts
|

Novel biocatalytic esterification reactions on fatty acids: synthesis of sorbitol 1(6) - monostearate

Abstract: Dedicated to Professor Sukh Dev on his 80th birthday (received 16 Jan 03; accepted 06 May 03; published on the web 08 May 03) AbstractAspergillus terreus lipase has exhibited novel capability of catalyzing esterification reaction between fatty acids (C 4 -C 18 ) and primary, secondary and tertiary monohydric alcohols. Although, the lipase efficiently catalyzed the esterification of saturated stearic acid (C 18:0 ), it failed to accept the monounsaturated oleic acid (C 18:1 ) as the substrate which is also a C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…In this study, lipase AY showed the selectivity toward the primary hydroxyl groups of the sorbitol moiety similar to that reported previously. , Thus, these results demonstrated that the position of alkyl substitution was not affected by the use of an aqueous biphasic reaction medium as compared to the organic solvent. Moreover, the acylation at the secondary hydroxyl group of the sorbitol moiety was shown to occur.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, lipase AY showed the selectivity toward the primary hydroxyl groups of the sorbitol moiety similar to that reported previously. , Thus, these results demonstrated that the position of alkyl substitution was not affected by the use of an aqueous biphasic reaction medium as compared to the organic solvent. Moreover, the acylation at the secondary hydroxyl group of the sorbitol moiety was shown to occur.…”
Section: Resultssupporting
confidence: 90%
“…According to previous studies, the acylation of hydroxyl groups of sugar/sugar alcohol moiety resulted in a downfield shift of the peak corresponding to the O-acylated carbon and an upfield shift of the peak corresponding to the neighboring carbons 5,45,46 . Based on this knowledge and a bi- In this study, lipase AY showed the selectivity toward the primary hydroxyl groups of sorbitol moiety similar to that reported previously 5,27 . Thus, these results demonstrated that the position of alkyl substitution was not affected by the use of an aqueous biphasic reaction medium as compared to organic solvent.…”
Section: Product Purification and Characterizationsupporting
confidence: 87%
See 2 more Smart Citations
“…Further increasing the molar ratio, the negative effect toward the conversion because the excess SL has blocked the active sites on the catalyst surface and subsequently prevent it from nucleophilic attack. 16 Despite the identical conversion at sixth hour, the M SL:AA of 4:1 was chosen and used for subsequent studies due to its superior initial rate of reaction. 3.1.3.…”
Section: G Rt K Lnmentioning
confidence: 97%